Educational Game Scenario Model Based On Imperative Game Goal Typology - Rickman Roedavan; Yahdi Siradj; Stella Stefany (Bina Nusantara University, 2023)
Educational games are digital products resulting from the application of game-based learning concepts. The main factors forming educational games include combining a learning subject with challenging elements and engaging visualization. Most educational games translate the challenge component of the game in the form of multiple choice quizzes, questions, answers, or puzzle solving. This result causes the mechanical structure of educational games less interesting than the mechanics of entertainment games. This paper proposes a scenario development model for educational games derived from the game goal typology commonly found in entertainment games. This model is expected to be a reference for developing educational game scenarios that can enrich the types of mechanics and increase the engagement of an educational game. The proposed model in the research has been tested on two educational games, both of which received high attractiveness scores of 1.632 and 1.542 respectively on the User Experience Question (UEQ) scale.